New technologies of detection of buried oil and gas structures (for example Ciscaucasia and North Caucasus zones) - Vladimir M. Kharchenko (Вестник Северо-Кавказского федерального университета, 2022)
The item offers a new technology, which is a paleo-structure-geomorphological method for detecting buried structures potentially containing oil and gas; the method is based on an analysis of the ancient relief elements based on the structural maps available and the geology-geophysical profiles of Ciscaucasia and North Caucasus.